Chicken feed optimization using evolution strategies and firefly algorithm - Andreas Nugroho Sihananto; M. Shochibul Burhan; Wayan Firdaus Mahmudy (International Journal of Electrical and Computer Engineering (IJECE), 2019)
Mixing broiler chicken and layer hens feed using various feed ingredients is a difficult task. The feed must fulfill the minimum nutrient requirement and must break the constraint. Some classic approach like Pearson’s Square has been already introduced to solve this problem. However, the approaches cannot guarantee to fulfill nutrient requirements and desirable price. The two metaheuristic algorithms Evolution Strategies (ES) and Firefly Algorithms (FA) are being proposed in this paper to know how well they performed this problems. Result show that ES is perform much better compared to classic Pearson’s Square, but ES itself is outperform by FA on both cases.